Analysis of Intellectual Capital on Company Financial Performance in PT Reethau Cipta Energy - Luthfi Hanif Pratama; Oetami Prasadjaningsih (Dinasti International Journal of Education Management And Social Science, 2024)
The research aims to investigate the relationship between intellectual capital of the key resource-based components of the company (physical capital, human capital and structural capital) with financial performance using ROA (return on assets), ROI (returns on investment), and GR (growth revenue). The data is sobtained from the financial reports of the company PT Reethau Cipta Energi for the period 2019 – 2021 and the results of employee questionnaires on a Likert scale. This study tested three elements of VAIC (value added intellectual capital) and measures the financial performance of an enterprise using partial least squares (PLS) for data analysis that showed that: (1) Intellectual Capital has a significant influence on Return on Assets (ROA). Intellectual Capital Affects Return on Investment (ROI). (3) Intellectual capital has a significant impact on Revenue Growth (GR). (4) Intellectual capital has no significant influence on overall financial performance.